The tidal model : a guide for mental health professionals - Barker, Philip J. (Brunner-Routledge, 2005)
Based on extensive research, The Tidal Model charts the development of this model of care, outlining its theoretical basis and including clinical examples to show the benefits of encouraging the client's greater involvement in their treatment.
Keywords: Mental health -- Philosophy.; Mental illness -- Philosophy.; Psychology, Pathological -- Philosophy.; Mental illness -- Treatment.; Mental Disorders -- therapy; Holistic Nursing -- methods; Persons with Psychiatric Disorders -- psychology.; Patient-Centered Care -- methods.; Psychiatric Nursing -- methods; Santé mentale -- Philosophie.; Maladies mentales -- Philosophie.; Psychopathologie -- Philosophie.; Maladies mentales -- Traitement.; MEDICAL -- Psychiatry -- General.; PSYCHOLOGY -- Psychopathology -- General.; PSYCHOLOGY -- Clinical Psychology.; PSYCHOLOGY -- Mental Illness.; MEDICAL -- Mental Health.; Mental illness -- Treatment; Mental health -- Philosophy; Mental illness -- Philosophy; Psychology, Pathological -- Philosophy; Geestelijke gezondheid.; Geestelijke gezondheidszorg.; Hulpverlening.